2021
DOI: 10.3390/microorganisms9061155
|View full text |Cite
|
Sign up to set email alerts
|

Selective Flamingo Medium for the Isolation of Aspergillus fumigatus

Abstract: For various studies in the clinic as well as the environment, it is essential to be able to selectively isolate Aspergillus fumigatus from samples containing bacteria as well as various other fungi (mainly Mucorales). Six agar media were compared for effectiveness in selectively isolating Aspergillus fumigatus from agricultural plant waste, woodchip waste, green waste, soil, grass and air samples collected in the Netherlands at a 48 °C incubation. The Flamingo Medium incubated at 48 °C, provided the most effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…These colonies could however still be readily identified as A. fumigatus by their compact and circular morphology. This was because few fungi other than A. fumigatus and morphologically distinct Mucorales species grew on the medium, as detailed in Zhang et al 2021. Figure 3: Visual examples of A. fumigatus growth on the sticky seals covered with Flamingo medium. Plates of most outdoor samples showed some Mucorales growth but not to a degree that hindered CFU counts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These colonies could however still be readily identified as A. fumigatus by their compact and circular morphology. This was because few fungi other than A. fumigatus and morphologically distinct Mucorales species grew on the medium, as detailed in Zhang et al 2021. Figure 3: Visual examples of A. fumigatus growth on the sticky seals covered with Flamingo medium. Plates of most outdoor samples showed some Mucorales growth but not to a degree that hindered CFU counts.…”
Section: Discussionmentioning
confidence: 99%
“…Under sterile conditions, the covers were removed from the seals and then individually placed in square Petri dishes with vents (120mmX120mmX17mm), sticky-side-up, again only touching the non-sticky strip with clean hands. Once all seals were placed in this manner, flamingo medium (Zhang et al 2021) was poured into the plate such that the entire seal and all of the plate was covered with a thin layer of medium. Crucially, the medium was prepared as described in (Zhang et al 2021) except that the medium, after the autoclaving step, was allowed to cool overnight in an incubator set at 60°C before adding the antimicrobial supplements and pouring the medium.…”
Section: Materials and Methods Sample Processing Culturing And Resist...mentioning
confidence: 99%
See 2 more Smart Citations
“…Culture remains the gold standard for the laboratory diagnosis of invasive fungal infections, including aspergillosis. Aiming to attain a higher sensitivity of cultures (especially in samples contaminated with different fungal genera), Zhang et al [ 1 ] suggested the use of Flamingo Medium as an efficient method for the isolating A. fumigatus , especially from tissue contaminated with fungi belonging to Mucorales order. The authors reported that, using Flamingo Medium, they were able to recover an average of 20−30% more A. fumigatus colonies compared to other media, and at the same time, a 95% reduction in the number of Mucorales colonies was also observed.…”
mentioning
confidence: 99%